Pengaruh Pemanfaatan Claystone Sebagai Alternatif Bahan Pengganti Agregat Halus Terhadap Kualitas Paving Block - Fikry Pandu Putranto; Irfan Prasetia (Jurnal Teknologi Berkelanjutan, 2021)
Claystone is rock contained generally of plastic, composed of a hydrous aluminum silicate (2H2OAL2O32SiO2) or fine grain size clay minerals. At the time of the construction of the Banjarbakula Regional TPA, there was found quite a lot of claystone material, of which there were more than 8000 m3 of claystone. Because they were not utilized properly, most of the claystone was removed and moved from the Banjarbakula Regional TPA. Therefore, it is necessary to reuse it, so the large amount of claystone material will not be wasted and can be optimally used. This study was conducted to determine the effect of claystone found in the Banjarbakula Regional TPA as an alternative to fine aggregate substitute for the quality of paving blocks and to determine the optimum mixture. In making paving block samples, variations of claystone were used as much as 0%, 25%, 50%, 75%, and 100% with water to cement ratio 0.4. The compressive strength test of paving block samples was carried out at the age of 7 and 28 days. Based on the results of the compressive strength test, the compressive strength value of paving blocks with 25% claystone mixture at the age of 28 days is 18.08 Mpa, which is the closest to the strength of normal paving blocks or without claystone mixtures of 18.24 MPa. The strength of a paving block with claystone mixture might increase with longer duration of the curing time.